La bête = The beast [videorecording (DVD)] - Bonello, Bertrand, 1968-; Charbit, Benjamin; Bréaud, Guillaume; Seydoux, Léa, 1985-; MacKay, George, 1992-; Malanda, Guslagie; James, Henry, 1843-1916 (Janus contemporaries., 2024)
By the year 2044, artificial intelligence reigns, and human emotions are a liability that must be surgically removed to produce a more pliant workforce. But this procedure triggers Gabrielle to experience haunting memories of her past lives, as she encounters different incarnations of her paramour, Louis, first in belle epoque Paris and then in 2014 Los Angeles. As she once more undergoes the pains and pleasures of romance and rediscovers what it means to be truly alive, Gabrielle awaits the erasure of her humanity with growing fascination and dread. In his most ambitious film yet, visionary director Bertrand Bonello freely adapts Henry James's novella The Beast in the Jungle into a visually stunning science-fiction labyrinth that is as metaphysically mysterious as it is emotionally powerful. Powered by Seydoux's heartrending performance, The Beast poignantly imagines the consequences of humankind becoming too afraid to risk the inherent vulnerability of love.